Optimising the DPPH Assay for Cell-Free Marine Microorganism Supernatants - Gang, Yehui (Mar Drugs, 2021)
Antioxidants prevent ageing and are usually quantified and screened using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. However, this assay cannot be used for salt-containing samples, such as the cell-free supernatants of marine microorganisms that are aggregated under these conditions. Herein, the DPPH solvent (methanol or ethanol) and its water content were optimized to enable the analysis of salt-containing samples, aggregation was observed for alcohol contents of >70%. The water content of methanol influenced the activities of standard antioxidants but did not significantly affect that of the samples. Based on solution stability considerations, 70% aqueous methanol was chosen as the optimal DPPH solvent. The developed method was successfully applied to the cell-free supernatants of marine bacteria (Pseudoalteromonas rubra and Pseudoalteromonas xiamenensis), revealing their high antioxidant activities. Furthermore, it was concluded that this method would be useful for the screening of marine microorganism–derived antioxidants, which also has numerous potential applications, such as salt-fermented foods.